2024
DOI: 10.1001/jama.2023.23248
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Naloxone for Opioid Overdose

Jessica L. Taylor,
Karen E. Lasser

Abstract: This JAMA Insights describes indications for naloxone use in preventing opioid overdoses and benefits vs barriers to its availability following FDA approval of its availability without a prescription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Opioid overdoses can be reversed by using the drug, naloxone. Naloxone is a competitive antagonist at the mu-opioid receptor that can be administered by many routes, including by bystanders and lay public via nasal spray ( Taylor & Lasser, 2024 ). The Centers for Disease Control and Prevention reported that, in 2019, a bystander was present in nearly 40% of opioid and stimulant overdose deaths ( O'Donnell et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Opioid overdoses can be reversed by using the drug, naloxone. Naloxone is a competitive antagonist at the mu-opioid receptor that can be administered by many routes, including by bystanders and lay public via nasal spray ( Taylor & Lasser, 2024 ). The Centers for Disease Control and Prevention reported that, in 2019, a bystander was present in nearly 40% of opioid and stimulant overdose deaths ( O'Donnell et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%